2021
DOI: 10.7717/peerj.12300
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptome analyses of differentSalvia miltiorrhizavarieties during the accumulation of tanshinones

Abstract: Salvia miltiorrhiza (Labiatae) is an important medicinal plant in traditional Chinese medicine. Tanshinones are one of the main active components of S. miltiorrhiza. It has been found that the intraspecific variation of S. miltiorrhiza is relatively large and the content of tanshinones in its roots of different varieties is also relatively different. To investigate the molecular mechanisms that responsible for the differences among these varieties, the tanshinones content was determined and comparative transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 59 publications
(66 reference statements)
0
3
0
Order By: Relevance
“…The comparative transcriptome analysis of the marijuana strain Purple Kush and the ‘Finola’ cultivar of Cannabis sativa demonstrated that the Δ9-tetrahydrocannabinolic acid synthase was detected in Purple Kush but replaced by cannabidiolic acid synthase in the ‘Finola’ cultivar, explaining the significant chemical difference between marijuana-derived Δ9-tetrahydrocannabinol (THC) and hemp-derived cannabidiol (CBD) ( van Bakel et al., 2011 ). Moreover, transcriptional changes during tanshinones accumulation stage among different varieties of Salvia miltiorrhiza expanded our vision on intraspecific variation and gene regulation mechanism of secondary metabolite biosynthesis pathways ( Zhou et al., 2021b ). Interestingly, platycodin D content of calli was higher than that of leaves in Platycodon grandiflorus , while platycoside E content of calli was lower than that of leaves.…”
Section: Functional Gene Mining Of Medicinal Plant Transcriptome To C...mentioning
confidence: 99%
“…The comparative transcriptome analysis of the marijuana strain Purple Kush and the ‘Finola’ cultivar of Cannabis sativa demonstrated that the Δ9-tetrahydrocannabinolic acid synthase was detected in Purple Kush but replaced by cannabidiolic acid synthase in the ‘Finola’ cultivar, explaining the significant chemical difference between marijuana-derived Δ9-tetrahydrocannabinol (THC) and hemp-derived cannabidiol (CBD) ( van Bakel et al., 2011 ). Moreover, transcriptional changes during tanshinones accumulation stage among different varieties of Salvia miltiorrhiza expanded our vision on intraspecific variation and gene regulation mechanism of secondary metabolite biosynthesis pathways ( Zhou et al., 2021b ). Interestingly, platycodin D content of calli was higher than that of leaves in Platycodon grandiflorus , while platycoside E content of calli was lower than that of leaves.…”
Section: Functional Gene Mining Of Medicinal Plant Transcriptome To C...mentioning
confidence: 99%
“…Frequently changing global climatic conditions with serious fluctuations in temperature regimes (high, low or very low temperature), uneven precipitation patterns leading to flooding or drought conditions, high humidity, significant shift in sunshine duration in winters and summers significantly regulate the plant performance in general with heavy yield penalties and specifically reduce the active ingredients and chemical composition in medicinal plants ( Zobayed et al., 2005 ; Manish, 2022 ; Patni et al., 2022 ; Appiah et al., 2023 ; Shaban et al., 2023 ; Shrestha et al., 2023 ; Theodoridis et al., 2023 ). The medicinal plant, Salvia miltiorrhiza Bunge also known as Danshen, belongs to the plant family Lamiaceae bears medicinal properties in traditional Chinese system of medicine to cure Alzheimer’s disease, myocardial infarction, and heart diseases including cerebrovascular diseases in various parts of China ( Miroddi et al., 2014 ; Ma et al., 2017 ; Cao et al., 2018 ; Ren et al., 2019 ; Guo et al., 2020 ; Zhou et al., 2021 ; Li et al., 2022 ). The root extract of Danshen contains chemical constituents which can be divided into liposoluble tanshinones (tanshinone I, tanshinone IIA (TsIIA), tanshinone IIB, cryptotanshinone, and dihydrotanshinone I) and water-soluble phenolics (salvianolic acids) ( Ma et al., 2015 ; Deng et al., 2019 ; Shi et al., 2019 ; Sun et al., 2019 ), Therefore, it becomes imperative to investigate and understand the response of different genotypes of Danshen under different climatic regimes.…”
Section: Genotype and Climatic Factors Impact On Rhizosphere Soil Pro...mentioning
confidence: 99%
“…Salvia miltiorrhiza Bunge (Lamiaceae) is an important medicinal plant in traditional Chinese medicine. Its dried roots and rhizomes have been used for the treatment of heart diseases including myocardial infarction, cerebrovascular diseases, and Alzheimer’s disease ( Zhou et al., 2021 ). The major active compounds in S. miltiorrhiza , water-soluble components (rosmarinic acid, and salvianolic acid B) and lipid-soluble components (tanshinone I, tanshinone ιI A, and cryptotanshinone), which are mainly accumulated in the roots and rhizomes ( Yang et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%